PENGARUH METODE TEAM GAME TOURNAMENT TERHADAP KEMAMPUAN HASIL SERVIS FOREHAND TENIS MEJA SISWA SMPN - Jumadi, Rino Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The problem in this research is how the influence of cooperative learning methods Team Games Tournament (TGT) on the ability of the results of learning basic techniques forehand service game of table tennis. The purpose of this study was to determine the effect on the ability of learning methods TGT learning outcomes forehand service. The method used in this study is experimental, true experimental forms of research, the data used in the form of observational results. The sample in this study amounted to 80 students. Based on the analysis of the influence of the test in the control group and the experimental value of 0.087 > 0.05 significance, so that the null hypothesis is accepted it means there are significant learning method tournament game against the team servicing capabilities table tennis forehand on the students of class VIII SMPN 13 Pontianak.Â Keywords: Team Game Tournament, Table Tennis.Â